The Participation of Private Healthcare in Malaria Prevention and Elimination: A Systematic Review - Dat, Le Minh; Phuong, Nguyen Trong Phuong; Son, Dao Anh; Dinh, Trinh My; Linh, Le Thi Thao; Son, Dang Cong; Anh, Nguyen Huu Duc (Health Dynamics, 2025)
Background: Malaria continues to pose a major public health threat globally, affecting millions and causing numerous fatalities annually. This research consolidates findings on private sector healthcare involvement in combating and preventing malaria across different nations. Methodology: A systematic review was conducted following PRISMA guidelines, extracting relevant studies from PubMed, ScienceDirect, Cochrane, and Semantic Scholar databases. Selection criteria included observational or interventional research examining private healthcare's role in malaria prevention, published in English between 2015-2024. Analysis was supported by NotebookLM. Results: The review identified 24 qualifying studies. Private healthcare providers, including clinics and pharmacies, contribute to malaria management through diagnosis, rapid testing, and treatment advice globally. Though these entities possess some malaria-related knowledge, it remains incomplete. Case reporting and surveillance participation exists among private providers but remains restricted to few facilities. Conclusions: Enhanced frameworks and regulations are essential to strengthen public-private partnerships and expand private sector engagement in malaria diagnosis, treatment, and advisory services. Implementation strategies should be tailored to each country's specific context and malaria epidemiology.